2018
DOI: 10.1097/hjh.0000000000001527
|View full text |Cite
|
Sign up to set email alerts
|

The value of uromodulin as a new serum marker to predict decline in renal function

Abstract: The current study is the first evaluating the value of uromodulin in serum as a novel predictive biomarker for renal function and for the incidence of CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 39 publications
6
46
0
1
Order By: Relevance
“…Finally, in the serial analysis, we found a direct correlation between better GFR and plasma Tamm‐Horsfall protein levels (also known as uromodulin). This fits well with previous studies showing uromodulin being protective and inversely associated with CKD …”
Section: Discussionsupporting
confidence: 93%
“…Finally, in the serial analysis, we found a direct correlation between better GFR and plasma Tamm‐Horsfall protein levels (also known as uromodulin). This fits well with previous studies showing uromodulin being protective and inversely associated with CKD …”
Section: Discussionsupporting
confidence: 93%
“…Although its antiinflammatory and renal protective properties in urine have long been known, the systemic function of UMOD remains elusive (8,9). Previous studies (10)(11)(12) have shown that lower serum UMOD (SUMOD) level is associated with a decline in kidney function in adults without diabetes. Further, lower SUMOD level has been linked with cardiovascular disease mortality in coronary patients (13,14).…”
mentioning
confidence: 99%
“…In summary, as several different UMOD SNPs have been linked to both CKD and eGFR, UMOD may prove to be useful as a diagnostic and prognostic genomic biomarker of CKD. Indeed, levels of serum uromodulin have recently been shown to useful in disease detection as CKD patients were shown to have a significantly lower serum uromodulin concentration (p < 0.001) and measurement of serum UMOD was shown to significantly enhance performance of a CKD prediction model (p = 0.049) [ 46 ]. UMOD often exhibits one of the strongest associations with CKD [ 22 , 26 ], suggesting that UMOD would likely be suitable as a diagnostic genomic biomarker of CKD.…”
Section: Genetic Biomarkersmentioning
confidence: 99%